The Effect of Flipped Classroom Size on Students' Critical Thinking Abilities - Everhard Markiano Solissa; Agus Triyono; Dharma Gyta Sari Harahap; Dewi Maharani Rachmaningsih; Novinaty Djafri; Asmawati Asmawati; Tomi Apra Santosa (Edumaspul: Jurnal Pendidikan, 2023)
purpose of this research is to determine the effect of flipped classroom size on students' critical thinking abilities. This type of research is meta-analysis. The data source comes from an analysis of 12 national and international journals published in 2018-2023. Data source search process via Google Scholar; ERIC, ScienceDirect, Wiley; ProQuest, DOAJ and EBSCO. Data selection using the PRISMA method consists of identification, screening, eligibility and inclusion. These findings conclude that the flipped classroom has a positive influence on students' critical thinking skills with a summary effect size value ( rRE= 0.799). The flipped classroom has a moderate influence on students' critical thinking abilities at school